Prevalence, trends and district differentials in teenage pregnancies - D Fernando; N Gundawardena; U Senarath; M Weerasinghe; C Galwaduge; C De Silva (College of Community Physicians of Sri Lanka, 2012)
Introduction Teenage pregnancies with their negative obstetric and foetal outcomes are a maternal and child health concern of the country. Objectives To study the prevalence, trends and district differentials in teenage pregnancies in Sri Lanka Methods Three main sources of available national level data were used in this study. They were : vital event registration data from the Registrar General's (RG) Department, data collected routinely by the Family Health Bureau (FHB), Ministry of Health through the Reproductive Health Information Management System (RHMIS) and data from the Demographic and Health Survey (DHS) 2006/07. Other than utilizing reported information of all three sources, primary data of DHS 2006/07 was accessed with permission and further analysis were performed. Results Routinely available data from the Registrar General's (RG) Department are based on the registrations of live births throughout the island, hence could be considered as a proxy for information on pregnancies. A consistent declining trend in pregnancies among women less than 19 years of age was observed from the year 2000 (8.1%) to 2006 (5.4%). Marked inter district variations were noted. The highest percentage of teenage pregnancy was among the Sri Lankan Tamils. The rural sector showed the highest percentages while the estate sector showed the lowest. High percentage of illegitimate births in the estate sector was noteworthy. Data from the routine RHMIS of the Family Health Bureau also showed a declining trend of teenage pregnant females registered by Public Health Midwives as a percentage of all registered pregnant mothers, during the period 2007 (7.7%) to 2010 (6.5%). The marked inter district variation was observed with the variations consistent to what was observed in the RG's data. Further analysis of DHS data showed that the percentage of teenage pregnancies among ever married women aged between 15 - 49 years to be 6.3% (95% CI 5.4-7.2). Teenage pregnancy rates declined significantly with increasing levels of education (p<0.0001) and with increasing wealth quintiles (p<0.0001). These findings are consistent with data from several other studies in the region. Inter district variations were similar to other two sources. Conclusions and recommendations Analysis of national level information related to teenage pregnancies from three different sources of available data showed that there is a declining trend in the prevalence of teenage pregnancies. All three sources identified that there is a marked inter-district variation in the teenage pregnancy rates and the districts identified to have high rates of teenage pregnancy by the three different sources were mostly consistent. This indicates the need for district specific interventions. Journal of the College of Community Physicians of Sri Lanka Volume 16, No. 02, December 2011 21-30 DOI: http://dx.doi.org/10.4038/jccpsl.v16i2.4577